Synthesis of novel crown ethers .1. Coumestan and coumestan analog derivatives of crown ethers - (:unkn) unknown (KLUWER ACADEMIC PUBL, 1996)
The presented ethylenedioxy compounds 5a, 5d, 6a and 6c are examples of novel cyclic ethers, while macrocyclic polyethers represent new crown ether analogues. New coumestan-crowns 5a-f, derivatives of 6, 7-dihydroxy-3, 4-dihydro-2H-dibenzofuran and 6, 7-dihydroxy-3, 3-dimethyl-3, 4-dihydro-2H-dibenzofuran-1-one 6a-e were synthesized from the corresponding o-dihydroxy compounds 3a-b, 4a-b and ditosylates or dichlorides of di- or triethylene glycol in the presence of K2CO3, in DMF/H2O (15/1) solutions at 65-75 degrees C for 35 hours. The structure of the macrocyclic ethers obtained were confirmed by H-1-NMR, C-13-NMR, IR spectra and elemental analyses.
Keywords: coumestan; coumarin; crown ethers; COUMARIN